THE EFFECT OF PRAYERS ON MENTAL HEALTH CONDITIONS IN CHILDREN AND ADOLESCENTS - Tri Wulandari; Masyitoh; Ridissa Queentari; Suhaimah; Saiful Bahri; Nahuda (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Prayer is one of the worships required by Allah SWT for the people of the Prophet Muhammad. Initially, the prayer was established so that the people of the Prophet Muhammad always remember Allah and be grateful for all the blessings given, until finally found many studies which state that the prayer movement can maintain and nourish a person's physical and psychological aspects. Prayer will help calm the mind and mood from worldly worries and anxieties. This research uses a library or literature review, which is research in the form of reviewing and observing a problem in depth. Prayer can help a Muslim to fight stress and fear, as Allah has promised in His word in the Qur'an. Prayer is also a drug to relieve anxiety so that the human soul becomes calmer and more peaceful in worship. Mental health is an excellent emotional and psychological state where individuals can utilize their cognitive and emotional abilities, function in their communities, and fulfill their daily needs. Prayer is the right solution to finding peace of mind and helping to find life's guidance.